The dark horse [videorecording (DVD)] - Robertson, James Napier; Curtis, Cliff, 1968-; Rolleston, James; Torrance, Kirk
"After years in and out of mental institutions, Genesis is released into the care of his older brother Ariki, a street gang leader. When he volunteers to train a group of disadvantaged Maori children for the upcoming National Chess Championships, it puts him at odds with his brother over Ariki's son Mana, whose interest in the game threatens the teen's imminent initiation into his father's violent gang. Despite all odds, Gen's positivity always leads him to search for light, even when the world seems at its darkest"--Container.